Effects of the functional HOTAIR rs920778 and rs12826786 genetic variants in glioma susceptibility and patient prognosis - Xavier-Magalhães, A (2017)
Abnormal expression of the long non-coding RNA HOX transcript antisense intergenic RNA (HOTAIR) is oncogenic in several human cancers, including gliomas. The HOTAIR single nucleotide polymorphisms (SNPs) rs920778 (C > T) and rs12826786 (C > T) present in the intronic enhancer and promoter regions of HOTAIR, respectively, are associated with expression, cancer susceptibility, and patient prognosis in some tumor types. However, the relevance of these HOTAIR SNPs has not been studied in glioma. Here, we report a case-control study comprising 177 Portuguese glioma patients and 199 cancer-free controls. All subjects were genotyped by PCR and restriction fragment length polymorphism (RFLP). No statistically significant differences were found in the genotype or allele distributions of either rs920778 or rs12826786 between glioma patients and controls, suggesting these SNPs are not associated with glioma risk. No significant associations were found between rs920778 variants and HOTAIR expression levels, while rs12826786 CT genotype was associated with increased intratumoral HOTAIR RNA levels when compared to TT genotype (p-value = 0.04). Univariate (Log-rank) and multivariate (Cox proportional) analyses showed both rs920778 CT and rs12826786 CT genotypes were significantly associated with longer overall survival of WHO grade III anaplastic oligodendroglioma patients. Our results suggest that HOTAIR SNPs rs920778 and rs12826786 do not play a significant role in glioma susceptibility, but may be important prognostic factors in anaplastic oligodendroglioma patients. Future studies are warranted to validate and expand these findings, and to further dissect the importance of these SNPs in glioma.